Flexural behavior of reinforced concrete T-section beams strengthened by NSM FRP bars. (15th April 2021) - Zhang, Y.; Elsayed, M.; Zhang, L.V.; Nehdi, M.L.
Highlights: Flexural behavior of RC T-section beams strengthened with NSM-FRP bars explored. Failure mode, load capacity, flexural stiffness, and ductility analyzed. Effects of concrete, reinforcement, and FRP bar were quantified. Analytical flexural strength predictions agreed with experimental results. New adjustment parameter to flexural stiffness prediction model was proposed. Abstract: Strengthening of deficient reinforced concrete (RC) beams using near surface mounted (NSM) fiber-reinforced polymer (FRP) bars has in recent years been gaining greater interest and increased field applications. While considerable research has explored the behavior of NSM-FRP strengthened rectangular-section RC beams and the effects of influential parameters, there is dearth of similar studies on RC T-section beams. Moreover, analytical models for predicting the flexural strength of NSM strengthened RC beams are yet to be confirmed experimentally. Thus, the present study investigates the behavior of RC T-section beams strengthened with NSM FRP bars under monotonic flexural loading and compares the experimental results with predictions of a flexural model derived from first principles. Ten RC T-section beam specimens strengthened with NSM FRP bars and three standard specimens were considered. The failure mode, cracking resistance, yielding, ultimate capacity, flexural stiffness, and ductility of specimens were compared and analyzed. Based on the experimental results, a general increase in flexural stiffness of the strengthened specimens was observed, especially at the post yield stage of loading. Analytical flexural strength predictions were calculated and corroborated with the experimental results. An adjustment parameter to the flexural stiffness prediction model was proposed to account for reductions in the effective area of the FRP bars used in the sectional strength calculations.